Implementing Contextual Teaching and Learning (CTL) Model to Teach Fiqh - dedi setiawan; Khodijah Khodijah; Ahmad Mansyur (Journal of Research in Islamic Education, 2020)
The problem of teaching Fiqh in Islamic Senior High School (Madrasah Aliyah) was lack of understanding of the student. It was happpend due to teacher did not provide real-world situations to facilitate students’ understanding. Therefore, to help the students to obtain optimal understanding, the Contextual Teaching and Learning model was implemented. It help students to make connections between their knowledge and its application in their lives as family and community members. The purpose of this research is: to determine the planning, the implementation and the assessment. The research was a qualitative research method with a case of study approach. Retrieval of informants using a purposive sampling system. The main informants in this study were the teachers of Islamic Civilization History, the vice principal of the curriculum field and the students of class XI State Islamic Senior High School (Madrasah Aliyah Negeri) Gumawang, Ogan Komiring Ulu Timur. The data collection techniques used observation, interview and documentation techniques. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. Based on the results of the study, it could be concluded that the implementation of the contextual teaching and learning model was run well, in its implementation there were three stages in implementing the model, namely the learning planning stage, the implementation stage. learning, and the contextual learning assessment stage